PENENTUAN JARAK STRUKTUR MATERI ANTARBINTANG LOOP I DAN LOOP II PADA LINTANG GALAKTIK SELATAN - Maulana, Ilham
One of components in the Galaxy is interstellar matter (ISM). Based on the two-dimensional mapping of ISM in radio wavelengths, the ISM distribution in the Milky Way Galaxy is more concentrated within the disk. However, at high galactic latitude, we can also find ISM as part of shell-like structures which are known as “loop”. Efforts to determine the distance of the loop structures have been carried out, but most of them studied the ISM in northern galactic latitudes or North Galactic Spur or North Polar Spur (NPS). The distance of these loop structures is under debate: is it local or non-local Galactic structure. In this final project, I determined the distance of Loop I and Loop II structures at the southern galactic latitude based on spectroscopic data from ESO and stellar parallaxes from GAIA EDR3. The interstellar tracers are interstellar absorption line NaI (D1 and D2) for the neutral ISM phase and CaII (H and K) for the ionized phase which are recorded in the reddened stellar spectra. The spectroscopic data are high-resolution spectra observed by using ESO – HARPS instrument. Stellar parallaxes of the target stars are used to constraint the ISM distance. I also estimated the ISM abundance by measuring the equivalent width of the identified interstellar lines by using Python package specutils.analysis.equi-valent_width. Based on this research, the distance of the ISM are started from approximately 30 parsecs, but in average the spectrum of target stars are contaminated by the ISM at 80 parsecs for Loop I and 60 parsecs for Loop II.